Dianetics the original thesis - Hubbard, L. Ron (La Fayette Ron) 1911-1986. (Los Angeles, California Bridge Publications, Inc., 2007)
L. Ron Hubbard's first and clearest description of Dianetics.
Sound discs contents: Introduction -- Primary axioms -- An analogy of the mind -- The dynamics -- The basic individual -- Engrams -- Aberrations -- The tone scale -- The character of engrams -- The auditor's code -- Auditing -- Diagnosis -- Exhaustion of engrams -- The analyzer -- The analyzer (cont) -- The clear -- Engram chains -- Dramatization -- Prenatal, birth and infant engrams -- The "laws" of returning.
"A Hubbard publication".
Includes bibliographical references and index.
Keywords: Dianetics